The Integration of Science and Religion:A Connectivity Education Conceptionofthe Islamic University: Integration of Science and Religion - Aris Mussnandar; Agus Salim (RAHMATAN LIL ALAMIN: JOURNAL OF PEACE EDUCATION AND ISLAMIC STUDIES, 2021)
Abstract: This article elucidates the changes of Islamic higher education institution In Indonesia. Building on this, the article describes a typology of Islamic education and its associated institutions. Influences of globalization in terms of the advancement of civilization and rapidly change in science and technology are also discussed. The discussion covers on a dichotomy between sciences and Islamic subjects that have to be delivered both in public universities and education institution based-Islam. The article seeks to delineate a conception of the integration between science and Islam that takes into consideration the Islamic Holy Book Al Qur’an and Prophetic statements, along with commonly-held approaches to education in Muslim history. This writing uses described qualitative research method. The experience of an Islamic University (UIN Maliki Malang) to implement new concept of educational management which is a combination between pesantren tradition and university (western tradition) will be explored in this writings. Keywords: Islamic education concept, The Integration Science and Islam